Ultimate interview : master the art of interview success with 100s of typical, unusual and industry-specific questions and answers - Williams, Lynn, 1955 January 15- (The Ultimate series, 2018)
In preparing for an interview, it's useful to understand what organizations are looking for in a candidate. Ultimate Interview offers insight into how employers decide what they are looking for in a job candidate, how they use this to draw up the questions, how selection procedures work, why employers conduct interviews and what's likely to happen at the average interview.